Effect of short-term carbohydrate overfeeding and long-term weight loss on liver fat in overweight humans. - Sevastianova, K; Santos, A; Kotronen, A; Hakkarainen, A; Makkonen, J; Silander, K; Peltonen, M; Romeo, S; Lundbom, J; Lundbom, N; Olkkonen, V; Gylling, H; et al. (2012)
BACKGROUND: Cross-sectional studies have identified a high intake of simple sugars as an important dietary factor predicting nonalcoholic fatty liver disease (NAFLD). OBJECTIVE: We examined whether overfeeding overweight subjects with simple sugars increases liver fat and de novo lipogenesis (DNL) and whether this is reversible by weight loss. DESIGN: Sixteen subjects [BMI (kg/m²): 30.6 ± 1.2] were placed on a hypercaloric diet (>1000 kcal simple carbohydrates/d) for 3 wk and, thereafter, on a hypocaloric diet for 6 mo. The subjects were genotyped for rs739409 in the PNPLA3 gene. Before and after overfeeding and after hypocaloric diet, metabolic variables and liver fat (measured by proton magnetic resonance spectroscopy) were measured. The ratio of palmitate (16:0) to linoleate (18:2n-6) in serum and VLDL triglycerides was used as an index of DNL. RESULTS: Carbohydrate overfeeding increased weight (±SEM) by 2% (1.8 ± 0.3 kg; P < 0.0001) and liver fat by 27% from 9.2 ± 1.9% to 11.7 ± 1.9% (P = 0.005). DNL increased in proportion to the increase in liver fat and serum triglycerides in subjects with PNPLA3-148IIbut not PNPLA3-148MM. During the hypocaloric diet, the subjects lost 4% of their weight (3.2 ± 0.6 kg; P < 0.0001) and 25% of their liver fat content (from 11.7 ± 1.9% to 8.8 ± 1.8%; P < 0.05). CONCLUSIONS: Carbohydrate overfeeding for 3 wk induced a >10-fold greater relative change in liver fat (27%) than in body weight (2%). The increase in liver fat was proportional to that in DNL. Weight loss restores liver fat to normal. These data indicate that the human fatty liver avidly accumulates fat during carbohydrate overfeeding and support a role for DNL in the pathogenesis of NAFLD. This trial was registered at www.hus.fi as 235780.